2020
DOI: 10.1186/s12875-020-01342-3
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ health information seeking behaviour – does the child’s health status play a role?

Abstract: Background Digital media are increasingly abundant providing a wide scope of health information. To date, very little is known about parental health information seeking behaviour for child health outside of English-speaking and Nordic countries. Our study “Digital parental counsellors” examines how parents search for health information in digital media, print media and among “personal contacts”, distinguishing between the search for information about general child health and development and chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…For example, the Apple and Google app stores differ in how apps are assessed for quality and how their search algorithms work, as well as in quality requirements for app developers [ 53 ]. As has been previously suggested, the mode in which information is presented matters [ 54 - 56 ], and this difference has the potential to affect how parents learn more about their child’s illness. In the same manner, the fact that there are apps that are available in one country but not in another also affects parents’ ability to find health information.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Apple and Google app stores differ in how apps are assessed for quality and how their search algorithms work, as well as in quality requirements for app developers [ 53 ]. As has been previously suggested, the mode in which information is presented matters [ 54 - 56 ], and this difference has the potential to affect how parents learn more about their child’s illness. In the same manner, the fact that there are apps that are available in one country but not in another also affects parents’ ability to find health information.…”
Section: Discussionmentioning
confidence: 99%
“…A 47-item survey developed from previously validated tools combined multiple-choice questions with optional open-text fields and Likert scales [22,23]. The first section explored parents' use of social media, the information sought, and motivations for using social media for child health information.…”
Section: Variablesmentioning
confidence: 99%
“…Previous research—not specific to the field of allergy prevention—focused on what prompts parents to seek health information ( 18 ) and what the topics of information searches are ( 19 ), such as understanding the basics of asthma and how to treat symptoms ( 20 ). Moreover, research concluded that parents start their (digital) searches most frequently via Google ( 19 ) and that, while they frequently use digital sources, HCPs remain a central, trusted source of information ( 21 ). For ECAP, it seems necessary to know not only which sources parents use and why, but also how they identify them and decide which to use, how they find them helpful, and how the information influences parents' decision-making.…”
Section: Introductionmentioning
confidence: 99%